LAMENT ŻAŁOBNY W KOPTYJSKIM EGIPCIE - Muc, Agnieszka (Śląskie Studia Historyczno-Teologiczne, 2023)
The lamentation ritual – filled with crying, dramatic gestures and shrieks – is common in many cultures. One of the best examples is ancient Egypt where this custom was part of qereset nefret – „the good/beautiful burial” – and is represented on many reliefs and paintings. This tradition was continued in Egypt in Greco-Roman period. Some literary sources suggest that the custom was also practiced in Christian times even though the Church officially banned it. The lives of St. Pachomius and St. Shenoute of Atripe mention that the monks were mourning at the moment of their superior’s death. The dirges recited by them contain two main elements: the praise of the dead and the complaint of the living who feel abandoned and call themselves orphans. This fact corresponds well with the ethnological data from many other cultures where the dirge is constructed of the same elements. The text of the dirge was placed sometimes on the Coptic funerary stelae. The inscriptions of this kind come from the Antinoe area and can be dated back to the second half of 8th century. Mostly they are autobiographical texts, describing death as a tragedy and using quotations from the Old Testament. They show similarities to many of the ancient Egyptian dirges. It is possible that the lamentation rituals were practiced in the Coptic period although the sources are too scant to state it with certainty or to describe the range of this custom in Christian times.